2015
DOI: 10.1155/2015/903164
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in theVesicular Monoamine Transporter 2Gene Decreases the Risk of Parkinson’s Disease in Han Chinese Men

Abstract: Background. Polymorphisms rs363371 and rs363324 in the vesicular monoamine transporter 2 (VMAT2) gene have been associated with risk of PD in an Italian population, and our aim is to investigate the association between the two single-nucleotide polymorphisms and PD in Han Chinese. Methods. 561 Han Chinese PD patients and 491 healthy age- and gender-matched controls were genotyped using Ligase detection reaction (LDR) method. Result. Both of patient and control groups showed similar genotype frequencies between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Furthermore, rare mutations in SLC18A2 result in infantile Parkinsonism [33][34][35] . In contrast, a number of studies have identified variants outside the coding region of SLC18A2 that increase expression of VMAT2 resulting in a gain-of-function and decreased likelihood of developing Parkinson's disease [36][37][38] . These studies suggest that increased sequestration of dopamine can be protective against the development of Parkinson's disease.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, rare mutations in SLC18A2 result in infantile Parkinsonism [33][34][35] . In contrast, a number of studies have identified variants outside the coding region of SLC18A2 that increase expression of VMAT2 resulting in a gain-of-function and decreased likelihood of developing Parkinson's disease [36][37][38] . These studies suggest that increased sequestration of dopamine can be protective against the development of Parkinson's disease.…”
Section: Discussionmentioning
confidence: 97%
“…In a low-VMAT-2-expression mouse model, locus coeruleus noradrenergic neurons exhibited progressive degeneration even before the onset of nigrostriatal DA neurodegeneration [57]. Conversely, polymorphisms identified in the human VMAT-2 promoter region indicated that elevated VMAT-2 expression correlated with reduced PD risk [58,59]. Notably, mice exposed during development to dieldrin, an environmental toxicant, displayed an increased DAT:VMAT-2 ratio in the adult nigrostriatal system and, consequently, were more vulnerable to MPTP toxicity than were unexposed control mice [60].…”
Section: How Does Sequestration Inside Neurons Determine Mpp + Toxicity?mentioning
confidence: 99%
“…A genetic study has found that alleles resulting in VMAT2 overexpression (rs363371 and rs363324) are associated with a lower risk of developing Parkinson’s disease in an Italian population [11]. A study with the Chinese Han population has replicated the result for the rs363371 allele in males, but not the other allele [12]. Another human study has reported gain-of-function VMAT2 haplotypes that result in overexpression of VMAT2 are associated with lower risk of developing Parkinson’s disease in females [13].…”
Section: Discussionmentioning
confidence: 99%
“…Our study aimed to identify compounds that could upregulate VMAT2 levels and activity since low VMAT2 levels are associated with BVMTD, Parkinson's disease, and depression, and high VMAT2 levels are protective for Parkinson's disease risk in Tricyclic and tetracyclic antidepressants upregulate VMAT2 activity… 4 humans and neurotoxicity in rodents [8][9][10][11][12][13][14][15][17][18]. We hypothesized that tricyclic antidepressants modulate VMAT2 activity since they are known to affect the monoamine transporters SERT and NET.…”
Section: Introductionmentioning
confidence: 99%